The Effect Of Right And Left Side Dribble Lay Up On The Students' Lay Up Ability Of Basketball Extracurricular Program - Rachmat Hidayat; Achmad Fahmi; Rasyidah Jalil (JUARA : Jurnal Olahraga, 2023)
Dribble is the most fundamental technique in basketball to improve the students' lay-up ability in the basketball extracurricular program at SMPN 8 Palopo. The mistakes occur when doing lay-ups, such as the first step, which needs to be longer, travelling and double. The study aims to determine the effect of right and left dribble lay-ups on the students' lay-up ability in basketball extracurricular programs. The method is experimental (Pretest-Posttest Design). The population is 20 students. The sampling technique is purposive sampling. The result of this research shows that there is a significant relationship between the right and left-side lay-ups of extracurricular basketball students. This research concludes that there is a substantial increase in students' lay-up ability at SMP 8 Palopo by applying right-side and left-side lay-up dribbles. Right-side lay-up dribble is more effective in increasing the extracurricular basketball students lay up capacity at SMPN 8 Palopo.